A biomimetic cartilage gradient hybrid scaffold for functional tissue engineering of cartilage. (June 2019) - Hu, Xueyan; Li, Wenfang; Li, Liying; Lu, Yanguo; Wang, Yiwei; Parungao, Roxanne; Zheng, Shuangshuang; Liu, Tianqing; Nie, Yi; Wang, Hongfei; Song, Kedong
Highlights: Cs and Gel can provide natural binding sites for cells, and produces no harmful products after degradation. It provides an important basis for the development of new gradient composite biomedical osteochondral repair materials. The growth of the cells on the gradient scaffold was superior to that of the control cells. Abstract: Osteochondral tissue has a complex layered structure that is not self-repairing after a cartilage defect. Therefore, constructing a biomimetic gradient scaffold that meets the specific structural requirements of osteochondral tissue is a major challenge in the field of cartilage tissue engineering. In this study, chitosan/Sodium β-glycerophosphate/Gelatin (Cs/GP/Gel) biomimetic gradient scaffolds were prepared by regulating the mass ratio of single layer raw materials. The same ratio of Cs/GP/Gel hybrid scaffold material was used as the control. Physical properties such as water absorption, porosity and the degradation rate of the material were compared to optimize the proportion of scaffold materials. P3 Bone Mesenchymal Stem Cells (BMSCs) were inoculated on the gradient and the control scaffolds to investigate its biocompatibility. Scanning electron microscopy (SEM) results show that 3:1:2, 6:1:3.5, 9:1:5, 12:1:6.5, 15:1:8 Cs/GP/Gel gradient scaffolds had excellent three-dimensional porous structures. Channels were also shown to have been interconnected, and the walls of the pores were folded. In the longitudinal dimension, gradient scaffolds had an obvious stratified structure and pore gradient gradualism, that effectively simulated the natural physiological stratified structure of real cartilage. The diameter of the pores in the control scaffold was uniform and without any pore gradient. Gradient scaffolds had good water absorption (584.24 ± 3.79˜677.47 ± 1.70%), porosity (86.34 ± 5.10˜95.20 ± 2.86%) and degradation (86.09 ± 2.46˜92.48 ± 3.86%). After considering the physical properties assessed, the Cs/GP/Gel gradient scaffold with a ratio of 9:1:5 was found to be the most suitable material to support osteochondral tissue. BMSCs were subsequently inoculated on the proportional gradient and hybrid scaffolds culture. These cells survived, distributed and extended well on the gradient and hybrid scaffold material. The biomimetic gradient scaffold designed and prepared in this study provides an important foundation for the development of new gradient composite biomedical materials for osteochondral repair.